Pin Row Loading Analysis of Scraper Conveyor under Oblique Cut Condition - Mao Jun; Tian Song; Chen Hongyue (Jixie chuandong)
According to the force analysis of roller,the equation set of roller in the process of cutting by three- axis force is derived.Combining the MATLAB programming,the curve of the before and after roller load changing with the rotation angle under the oblique cut condition is obtained.With shearer machine as the research object,the whole machine mechanical equation is listed,the mathematical computing model is established.Based on MATLAB programming,combining with the before and after roller load changing curve under the oblique cut condition,the before and after sliding shoe load curves under the oblique cut condition is obtained.Due the contact relation between the sliding shoe and pin row and the principle of force mutual action,the curve of load acting on the pin rows under the oblique cut condition is achieved.And through the ANSYS Workbench simulation analysis,the stress distribution and deformation of pin rows of scraper conveyor are got.A reference for the future of design and analysis of damage causes of scraper conveyor pin row is provided.